Understanding the gender gap among turn-of-the-century Swedish compositors - Joyce Burnette; Maria Stanfors (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2018)
Women have always earned less than men, with men's greater physical strength explaining a large portion of the difference. This raises the question of why the gender gap did not disappear when the importance of physical strength waned with the emergence of the modern labor market. This paper explores the wage gap among Swedish compositors, an occupation featuring the main traits of modernity, circa 1900. We exploit matched employer-employee data with national coverage,and examine information on men and women holding the same jobs. On average, women's hourly wage was about 70 percent of men's. Individual characteristics explain much, but not all, of this gender gap. To explain the remainder of the gap, we examine training and differences across firms. Our findings suggest that women received less training than men, and accounting for differences across firms explains the gender gap. We also find differences across firms by size and location. Smaller firms outside the major cities treated men and women fairly, but large firms in big cities did not offer women the same opportunities as men, creating a gender wage gap. These results are consistent with the hypothesis that firms which set up internal labor markets treated men and women differently.
Keywords: J16; J31; 330; Gender; earnings; manufacturing industry; firm-level data